Pengaruh Citra Merek Dan Daya Tarik Terhadap Loyalitas Produk Nivea Di Piayu Kota Batam - Siagian, Gebby Mirayu; Realize, Realize (SCIENTIA JOURNAL, 2023)
This study aims to analyze the effect of brand image and attractiveness on Nivea productloyalty in Piayu, Batam City. This research method uses descriptive research with aquantitative approach. The population of this study are consumers who use Nivea productsand live in the Tanjung Piayu sub-district, Sei Beduk sub-district, Batam City. The totalnumber of consumers in the area reached 10,649 people. The technique of determiningthe sample through the Slovin formula with the calculation results of 386 respondents isbased on simple random sampling. Data analysis techniques using descriptive statisticaltests, data quality tests, classical assumption tests, influence tests and hypothesis testing.The findings in the multiple linear regression analysis state that brand image has a positiveeffect on loyalty with an effect size of 31%. Attractiveness has a positive effect on loyaltywith an influence size of 21.2%. The results of the analysis of the coefficient ofdetermination (R2) state that brand image and attractiveness can explain loyalty, with aneffect of 8.9%. The results of the t and F tests show that brand image and attractivenesshave a positive and significant effect partially and simultaneously on loyalty decisions